Paying the price for the meat we eat. Issue 97 (July 2019) - Allen, Andrew M.; Hof, Anouschka R.
Highlights: Meat consumption and intensive agricultural practices threaten biodiversity. Policy changes are needed to encourage environmentally friendly farming. Biodiversity offsetting compensates the ecological damage of new developments. We propose biodiversity offsetting as a policy tool to reduce agriculture impacts. Urgent actions are needed to alleviate looming planetary crises. Abstract: An increasingly gloomy picture is painted by research focusing on the environmental challenges faced by our planet. Biodiversity loss is ongoing, landscapes continue to transform, and predictions on the effects of climate change worsen. Calls have been made for urgent action to avoid pushing our planet into a new system state. One of the principal threats to biodiversity is intensive agriculture, and in particular the livestock industry, which is an important driver of greenhouse gas emissions, habitat degradation and habitat loss. Ongoing intensification of agricultural practices mean that farmland no longer provides a habitat for many species. We suggest the use of a growing policy tool, biodiversity offsetting, to tackle these challenges. Biodiversity offsetting, or ecological compensation, assesses the impacts of new development projects and seeks to avoid, minimise and otherwise compensate for the ecological impacts of these development projects. By applying biodiversity offsetting to agriculture, the impacts of progressively intensifying farming practices can be compensated to achieve conservation outcomes by using tools like environmental taxes or agri-environment schemes. Low intensity, traditional, farming systems provide a number of benefits to biodiversity and society, and we suggest that the consumer and the agriculture industry compensate for the devastating ecological impacts of intensive farming so that we can once again preserve biodiversity in our landscapes and attempt to limit global temperature rise below 2°c.